Health Management: Occupational Therapy 's Key Role in Educating Clients About Reliable Online Health Information - Amy Armstrong-Heimsoth; Melissa L. Johnson; Meredith Carpenter; Tincey Thomas; Ashley Sinnappan (Scholarworks @ WMU, 2019)
Background: Only 12% of Americans possess proficient health literacy skills. Among those with the lowest health literacy are individuals with chronic health conditions. Occupational therapists are well prepared to assist these clients with health literacy, given our roles in teaching new health management skills and health promotion. Methods: An educational course was designed and taught to over 100 individuals and caregivers with chronic health conditions to assist in finding and determining trustworthy health information online. An author designed pre postsurvey was used to evaluate effectiveness. Results: There was a significant pre-post change in four categories: finding quality health information online (M = 0.703), judging trustworthiness of online health information (M = 0.624), understanding health information (M = 0.489), and retrieving information using email alerts (M = 0.826). Conclusion: The ability to find and evaluate health information online empowers clients to fully participate in medical care. Evidence shows that this skill can be efficiently taught to clients or client groups for improved health management. Providing training in finding trustworthy health information online is a skill that occupational therapists can successfully teach in conjunction with overall health management skills for improved occupational participation.